The Problem of Revenue-Sharing Principles in Indonesian Islamic Banking based on Smart Theory - Dedy Rachmad; Asmuni Asmuni; Sugianto Sugianto (Khazanah Sosial, 2022)
The problem of implementing the principle of revenue sharing in Indonesian Islamic banking until now has not found a bright spot. It was found that some Islamic banks closed their revenue-sharing products, especially mudharabah agreements. Related to this, in an effort to accommodate the wishes of customers/prospective customers and the interests of Islamic banks, there needs to be a theory that is considered able to bridge the interests of both parties. This paper tries to meet those demands, whereby a review of smart theory literature appears and becomes the main choice in the search for literature because this article provides a qualitative descriptive summary. This paper will also develop new concepts and theories in order to complement existing theories. The results of the analysis show that smart theory has a role in accommodating the interests of Islamic banks and customers/prospective customers, but the theory developed is still conventionally charged, so it cannot be fully applied in solving the problem of revenue sharing principles in Indonesian Islamic banking. Therefore, the new theory created is to combine smart theory with maslahat theory using several approaches such as ease aspects, aspects of supervision, religious aspects, social aspects, and methodological aspects in terms of flexibility.